KRITERIA HADIS HASAN MENURUT AL-SUYûTî DALAM AL-JâMI‘ AL-SAGHîR - Suhendra, Ahmad (Mutawatir : Jurnal Keilmuan Tafsir Hadith, 2014)
Post Rasulallah died, Islam continues to evolve from scientific and territorial aspects. Tradition as handed down by his teachings was widespread along with it. However, it should be unfortunate, as a result of many factors, the traditions that developed in the Islamic community also infected by a handful of people. At that time already occurred forgery traditions anchored in the Rasulallah. Therefore, to maintain the authenticity of the hadith of the Prophet, the scholars formulate certain criteria in determining the authenticity of a hadith. al-Jâmi? al-Saghîr is one of the books of hadith are considered in the study of hadith. This book is one that is referred to in the hadith search (takhrîj hadîth). al-Suyûtî collect a wide range of hadith from various sources in the book, so that it does not only exist but also the hadîth sahîh but also there is the hadîth hasan. That is the reason this article examines hadîth hasan in al-Jâmi? al-Saghîr. Based on the research of al-Suyûtî in al-Jâmi? al-Saghîr not provide new criteria in the hadîth hasan, but he became a mediator between scholars have different opinions in determining the status of the hadith.